Penggunaan Pupuk Organik dan KCl pada Tanaman Bawang Merah (Allium ascalonicum L.) - Husna Yetty; Evawani Elita (Jurnal Sagu, 2008)
The purpose of research was to know the influence of organic manure and KCl to the growth and suitable/recommended dosage for the manure combination. This research was executed by factorial experiment (Randomized Complete Block Design) with two factors and three replications. The parameters controlled were height of plant, amount of corm, wet weight and dry weight. The result explained that interaction between organic manure and KCl significantly influenced amount of corm, wet weight and dry weight, but did not significantly influenced the plant height. Organic manure and 250 kg/ha KCl was the best treatment for all parameters.